Moderating effect of budget implementation on the relationship between selected local government characteristics and the provision of primary education in Kaduna State, Nigeria - Usman, Mohammed (2022)
This study examines the moderating effects of statutory fund allocation, leadership behaviour and managerial accountability on budget implementation by the local government for the provision of primary education in the state of Kaduna, Nigeria. The study was motivated by public outcries over the declining quality of primary education delivered and managed by the local governments in the country. A conceptual framework and a model were developed based on the gaps in the reviewed literature. This study employed public choice and human capital theories to explain the relationships among the constructs of the study. Self-administered survey method via structured questionnaire and triangulated interviews had been conducted to collect data from local government staff, primary school teachers and pupils’ parents in the Kaduna State. Stratified sampling was used to select 538 respondents from the total population of 30,104 teachers and local government staff. Both SPSS 20 and PLSSEM 3.0 were employed for analysis purposes. This study employed the triangulation approach by corroborating information from multiple sources as it improves the accuracy of information and data. The research findings show the direct relationships between the statutory fund allocation, leadership behaviour, managerial accountability and budget for primary education allocated by the local government in the Kaduna State. Moreover, moderating relationship reveals that the budget implementation significantly moderates the relationship between leadership behaviour and funding provision of primary education by local government in that state. Triangulated interviews conducted in this study confirmed the findings of the above direct and moderated relationships. However, the budget implementation by the local government for the provision of primary education did not moderate statutory fund allocation and managerial accountability. This study suggests that the local governments in the Kaduna State in particular, and Nigeria as a whole, should ensure adequate funding, inculcate managerial accountability, proactive leadership behaviour and proper budget implementation by local governments so as to provide an effective primary education system. Finally, this research has also discussed the limitations, contributions, implications of the study and necessary suggestions on new research grounds and recommendations for policymakers and stakeholders on primary education.